642 PL02.01 DOES A HIGH MANDARD SCORE REALLY DEFINE A POOR RESPONSE TO CHEMOTHERAPY IN OESOPHAGEAL ADENOCARCINOMA?. (17th September 2021) - Knight, William; Baker, Cara; Griffin, Nyree; Kelly, Mark; Davies, Andrew; Gossage, James
Abstract: : A high Mandard score corresponds to a non-response to chemotherapy in the primary tumour in oesophageal adenocarcinoma. However, some patients experience tumour volume reduction and a nodal downstaging despite a high score. This study compares survival and recurrence patterns in these patients. Methods: Clinicopathological factors were analysed using multivariable Cox regression assessing time to death and recurrence. CT estimated tumour volume change was examined in a subgroup of consecutive patients. Mean pre-chemotherapy and post chemotherapy tumour volumes were compared across Mandard groups and nodal responders. Results: 555 patients were included. Median survival was 55 months (Mandard 1, 2, 3) and 21 months (Mandard 4, 5). In the Mandard 4, 5 group (332 patients), comparison between complete nodal responders and persistent nodal disease showed improved survival (90 vs 18 months), recurrence rates (locoregional 14.75% vs 28.74, systemic 24.59% vs 48.42%) and CRM positivity (22.95% vs 68.11). Complete nodal response independently predicted improved survival (HR 0.34(0.16–0.74). Post-chemotherapy tumour volume reduction was greater in patients with a complete nodal response (−16.3 cm3 vs −7.7 cm3 p 0.033) with no significant difference between Mandard groups. Conclusion: Patients with a complete nodal response to chemotherapy have significantly improved outcomes despite a poor Mandard score. High Mandard score does not correspond with a non-response to chemotherapy in all cases and patients with nodal downstaging may still benefit from adjuvant chemotherapy.